2017
DOI: 10.1590/1679-78253414
|View full text |Cite
|
Sign up to set email alerts
|

Application of Short Fibers Reinforced Composites in Power Transmission Coupling

Abstract: In this study the use of short glass, carbon and hybrid glass-carbon fibers reinforced polymeric composites in power transmission coupling is investigated. The presented work is generalized to thermoplastic and thermoset polymeric matrix composites. The effects of the constituents weight percentages, and average fibers length on the composite tensile strength and modulus are studied using the Taguchi design of experiments method. A new approach of Finite Element analysis is introduced to model the effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…This increase was attributed to the densification of the composites due to the use of the filler and the application of high pressure during the molding process. Similar results were observed by Hamza et al 56 Behavior that can also be explained by the length of the fibers used, since using short fibers it is possible to obtain a greater density of fibers in mass or in volume, in relation to long fibers and, therefore, it is possible to reduce the areas without fibers, that is, the distance between fibers, as can be seen in other studies Chung et. al, 25 Graupner et al, 26 and Mortzavian et al 27 Migneault et al 28 in studies indicated that fiber length has a significant effect on WPC density.…”
Section: Resultssupporting
confidence: 88%
“…This increase was attributed to the densification of the composites due to the use of the filler and the application of high pressure during the molding process. Similar results were observed by Hamza et al 56 Behavior that can also be explained by the length of the fibers used, since using short fibers it is possible to obtain a greater density of fibers in mass or in volume, in relation to long fibers and, therefore, it is possible to reduce the areas without fibers, that is, the distance between fibers, as can be seen in other studies Chung et. al, 25 Graupner et al, 26 and Mortzavian et al 27 Migneault et al 28 in studies indicated that fiber length has a significant effect on WPC density.…”
Section: Resultssupporting
confidence: 88%